Prospects and Current Status of Defence Information Security in Ukraine - Olha O. Zolotar; Mykola M. Zaitsev; Vitalii V. Topolnitskyi; Kostiantyn I. Bieliakov; Ihor M. Koropatnik (Faculty of Law, Hasanuddin University, 2022)
Relevance of the article - security has always been one of the priority issues of state policy. Considering that the defence forces are an inseparable part of state security, studying their information security is essential. The feasibility of this study is confirmed by the fact that in the current conditions of development of the information society, the information technology of the Ukrainian defence forces must adapt to the current challenges and threats, to ensure proper protection of information of strategic importance to the state and collected, consolidated and stored by the defence forces. This article aims to identify problems of information security of defense forces in Ukraine to find ways of their elimination. Formal logical, systemic structural, comparative and legal methods were used to conduct the research. It is stated that by dividing the information space and cyber space, the legislator has laid down legal regulation of protection of the state's information space. It is understood that the Lithuanian and Latvian forces for combating threats to the information space were consolidated within the structure of the Ministry of Defence. Consequently, the authorities argue that the system of entities responsible for protecting the information space needs to be optimized, creating conditions for state-private cooperation in this area, as in the case of Germany, and providing these entities with qualified employees. The results obtained are important for research, law-making and law enforcement activities.